Subsurface Alteration Characteristics Due to Hydrothermal Influence Using the Geoelectrical Method in the Ie Seu’um Geothermal Area, Aceh Besar - Hasana, Nur; Sugiyanto, Didik; Muksin; Syukri, Muhammad (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Research on subsurface alteration due to hydrothermal fluid influence was conducted in the hydrothermal manifestation area of Mesjid Raya District, Aceh Besar, Aceh. Data was acquired using the electrical resistivity method with a Wenner–Schlumberger configuration along four survey lines. Survey Lines 1 and 2, each 106.5 m long with 1.5 m electrode spacing, represent Zone 1, which is located directly at the hot spring source. Survey Lines 3 and 4, each 210 m long with 3 m electrode spacing, represent Zone 2, located 3.5 km from Zone 1 and 2 unaffected by hot fluid flow. This study aimed to identify the geothermal influence on subsurface characteristics. The results revealed clear differences in the resistivity profiles between Zones 1 and 2, with resistivity variations ranging from 0–600 Ωm and 0–5000 Ω·m, respectively. Interpretation indicates that Zone 1 consists of hydrothermally altered volcanic rocks, while Zone 2 comprises alluvium affected by weathering in the unsaturated (vadose) zone under meteoric water influence. These subsurface alterations provide essential evidence of geothermal impacts on rock characteristics. The findings also support the interpretation that the Ie Seu’um geothermal system is strongly concentrated in Zone 1, whereas surrounding areas show weaker manifestations that do not support the development of an active geothermal system.